Anti-tumour necrosis factor therapy in rheumatoid arthritis and risk of malignant lymphomas: relative risks and time trends in the Swedish Biologics Register. Issue 5 (8th May 2008) - Askling, J; Baecklund, E; Granath, F; Geborek, P; Fored, M; Backlin, C; Bertilsson, L; Cöster, L; Jacobsson, L T; Lindblad, S; Lysholm, J; Rantapää-Dahlqvist, S; et al.
Abstract : Background: Tumour necrosis factor (TNF) antagonists have proved effective as treatment against rheumatoid arthritis (RA), but the unresolved issue of whether the use of anti-TNF therapy increases the already elevated risk of lymphoma in RA remains a concern. Methods: Using the Swedish Biologics Register (ARTIS), the Swedish Cancer Register, pre-existing RA cohorts and cross-linkage with other national health and census registers, a national RA cohort (n  =  67 743) was assembled and patients who started anti-TNF therapy between 1998 and July 2006 (n  =  6604) were identified. A general population comparator (n  =  471 024) was also assembled and the incidence of lymphomas from 1999 to 31 December 2006 was assessed and compared in these individuals. Results: Among the 6604 anti-TNF-treated RA patients, 26 malignant lymphomas were observed during 26 981 person-years of follow-up, which corresponded to a relative risk (RR) of 1.35 (95% CI 0.82 to 2.11) versus anti-TNF-naive RA patients (336 lymphomas during 365 026 person-years) and 2.72 (95% CI 1.82 to 4.08) versus the general population comparator (1568 lymphomas during 3 355 849 person-years). RA patients starting anti-TNF therapy in 1998–2001 accounted for the entire increase in lymphoma risk versus the two comparators. By contrast, RR did not vary significantly by time since start of first treatment or with the accumulated duration of treatment, nor with the type of anti-TNF agent. Conclusion: Overall and as used in routine care against RA, TNF antagonists are not associated with any major further increase in the already elevated lymphoma occurrence in RA. Changes in the selection of patients for treatment may influence the observed risk.